2022
DOI: 10.24903/ajip.v9i2.988
|View full text |Cite
|
Sign up to set email alerts
|

Robusta Coffee Growth Response to Application of Various Liquid Organic Fertilizers in Replacing C-Organic and N-Total Soil

Abstract: The Ministry of Agriculture through the Agricultural Quarantine Agency (2019) stated that Robusta coffee has contributed 41% of the country's foreign exchange, with an average export frequency of 102 times per month, and will continue to increase. In connection with the growth in export volume of robusta coffee, coffee farmers need additional substances for the soil in the form of nutrients to be able to meet the soil nutrient needs for coffee from planting to harvest. Organic fertilizer in liquid form is one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Based on the results of studies conducted, it is stated that Donald Super's career theory is effective in increasing student self-efficacy and career commitment, besides Donald Super's career theory has also been proven to be effective for increasing vocational students' work readiness (Mutmainah & Arumsari, 2020). Through this study, it can be concluded that Donald Super's career theory can improve the job readiness of vocational students so that at the tertiary level individuals have work readiness that leads to a high level of self-efficacy and commitment so that individuals will live their careers well.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the results of studies conducted, it is stated that Donald Super's career theory is effective in increasing student self-efficacy and career commitment, besides Donald Super's career theory has also been proven to be effective for increasing vocational students' work readiness (Mutmainah & Arumsari, 2020). Through this study, it can be concluded that Donald Super's career theory can improve the job readiness of vocational students so that at the tertiary level individuals have work readiness that leads to a high level of self-efficacy and commitment so that individuals will live their careers well.…”
Section: Resultsmentioning
confidence: 99%
“…The most widely cultivated coffee in Indonesia is Robusta coffee. Robusta coffee production in Indonesia reaches 90% and the remaining 10% is Arabica coffee (Mutmainah, 2020). However, Robusta coffee has a lower quality than other types of coffee.…”
Section: Introductionmentioning
confidence: 99%